The Implementation of Gallery Walk Method to Improve Social Studies Learning Outcomes Grade VIII at SMPN 20 Jakarta - Fuji Ochtaulia; Desy Safitri; Sujarwo Sujarwo (Indonesian Journal of Innovation Multidisipliner Research, 2026)
This study was motivated by the low learning outcomes at social studies subject of eight grade-state in SMPN 20 Jakarta. In the process of learning, varied learning methods are still not used and dominated by teacher-based-learning which caused students to be less active and low in learning outcomes of social studies subject. The research method used was Classroom Action Research (CAR) based on the Kemmis and McTaggart model, which was conducted in two cycles with each cycle consisting of the stages of planning, action implementation, observation, and reflection. The research subjects is 36 students of class VIII-I with 16 males dan 20 females in the 2025/2026 academic year. The result shows that the implementation of Gallery Walk methods could improve the learning outcomes and participations of class VIII-I students. Seen from the percentage, where in cycle 1 reached 75% with an average score 85 and increased to 83% with an average score 90 in cycle 2. The student participation also showed improvement in the aspect asking questioning, answering questioning, expressing oppinions, and collaboration. From the research result, it showed that the Gallery Walk methods could improve learning outcomes and student participation of social studies subject of eight grade-state in SMPN 20 Jakarta.